The future low-temperature geochemical data-scape as envisioned by the U.S. geochemical community. (December 2021) - Brantley, Susan L.; Wen, Tao; Agarwal, Deborah A.; Catalano, Jeffrey G.; Schroeder, Paul A.; Lehnert, Kerstin; Varadharajan, Charuleka; Pett-Ridge, Julie; Engle, Mark; Castronova, Anthony M.; Hooper, Richard P.; Ma, Xiaogang; et al.
Abstract: Data sharing benefits the researcher, the scientific community, and the public by allowing the impact of data to be generalized beyond one project and by making science more transparent. However, many scientific communities have not developed protocols or standards for publishing, citing, and versioning datasets. One community that lags in data management is that of low-temperature geochemistry (LTG). This paper resulted from an initiative from 2018 through 2020 to convene LTG and data scientists in the U.S. to strategize future management of LTG data. Through webinars, a workshop, a preprint, a townhall, and a community survey, the group of U.S. scientists discussed the landscape of data management for LTG – the data-scape. Currently this data-scape includes a "street bazaar" of data repositories. This was deemed appropriate in the same way that LTG scientists publish articles in many journals. The variety of data repositories and journals reflect that LTG scientists target many different scientific questions, produce data with extremely different structures and volumes, and utilize copious and complex metadata. Nonetheless, the group agreed that publication of LTG science must be accompanied by sharing of data in publicly accessible repositories, and, for sample-based data, registration of samples with globally unique persistent identifiers. LTG scientists should use certified data repositories that are either highly structured databases designed for specialized types of data, or unstructured generalized data systems. Recognizing the need for tools to enable search and cross-referencing across the proliferating data repositories, the group proposed that the overall data informatics paradigm in LTG should shift from "build data repository, data will come" to "publish data online, cybertools will find". Funding agencies could also provide portals for LTG scientists to register funded projects and datasets, and forge approaches that cross national boundaries. The needed transformation of the LTG data culture requires emphasis in student education on science and management of data. Highlights: Scientists use a wide variety of data repositories for heterogeneous LTG datasets. Both structured and unstructured databases are needed to store LTG data online. Powerful search tools and data portals are needed to enable LTG data discovery.